AT THE CROSSROADS OF LINGUISTIC CULTURES: THE PROBLEM OF CREATION OF THE AZERBAIJANI LANGUAGE BRIEF COURSE FOR THE FOREIGN STUDENTS STUDYING IN THE NON-STATE LANGUAGES IN AZERBAIJAN - Musabayova, Narmin (International Journal of Innovative Technologies in Social Science, 2021)
The article raises the question of the need of the Azerbaijani language for the foreign students studying in Azerbaijan in the non-state languages. The author connects the efficiency of the educational process with confronting the challenges of socio-cultural, learning and psychosocial adaptation of foreigners to the current realities. The author stresses the importance of a nationally-owned Brief Course of the Azerbaijani language for foreign students studying in the non-state languages in the Preparatory Departments of the Azerbaijani universities. As an example, the author refers to her own Program of the Brief Course of the Azerbaijani language for the Chinese students studying in Russian.In the proposed Program, the author indicates a specific lexical and grammatical material, examples of dialogues for conversations that should be assimilated by students. In the last part of the study, educational recommendations to the teachers are suggested and it is also noted the contribution of the ASUOI’s teachers of the Russian language as a foreign language in the drawing up the first Program and textbooks on teaching the Azerbaijani language as a foreign language.